Pollen viability and germination of parental lines of onion hybrids - Affonso Lorenzon, Maria Cristina; Cruz de Almeida, Élcio (Pesquisa Agropecuaria Brasileira, 1997)
Experiments were conducted in Igarapé, MG, Brazil, on hybrid onion culture, and in Viçosa, MG, to investigate the fertility of parental lines of hybrid onion. Pollen viability was tested by contrast with acetic carmine. The germinate capacity was studied in the following culture media: a) saccharose 5% solution; b) saccharose 10% solution; c) 50 ppm solution of boric acid + 0.5 g of agar + 10 g of saccharose. The germinated pollen formed a contrast with "azul-de-amã". Lipids were observed in the presence of sudam IV. The production of hydrid seeds per flower under conditions of natural and artificial polinization was evaluated. By the acetic carmine test, the pollen showed to be viable, but did not germinate adequately in culture medium. There are factors which interfer negatively with its fertility. In the field, pollen germination in the stigma of the sterile male lines was satisfactory. The presence of lipids in the pollen and in the stigma showed the importance of the action of insect pollinators in this flowering.
Keywords: Allium cepa; fertility; acetic carmine; fat; saccharose; seeds